Enrichment, Isolation and phylogenetic identification of cholesterol-degrading fungi - Mthakathi, Ntsane Trevor (Bloemfontein: Central University of Technology, Free State, 2016)
Cholesterol is one of the most abundant lipids playing crucial role in the physiology of humans. This precursor of vitamin D, steroid hormones and bile acids maintains structural integrity and the fluidity of the lipid bilayer and also possess a tremendous role in cellular signalling. Plants also synthesize close homologs of cholesterol collectively called phytosterols, which play a crucial role in plant physiology. The significance of cholesterol is not only in maintaining normal physiology in eukaryotic organisms as its main producers. For over 70 years, bacteria have been the only group of microorganisms known and demonstrated to degrade or biotransform or utilize cholesterol as the source of carbon and energy. The etiologic agent of tuberculosis, Mycobacterium tuberculosis, uses human cholesterol as the carbon and energy source to survive and cause the disease. Cholesterol degradation pathway and enzymes involved in the degradation is under immense study to use as novel drug targets. The current study is the first of its kind in fungal lipid research, bringing a novel concept of cholesterol utilization by fungi. In this study, four fungal strains able to utilize cholesterol as the sole source of carbon and energy were isolated from South African soil. The fungal strains were identified using the three ribosomal subunits 5.8S rRNA, 18S rRNA and 28S rRNA gene sequences. Based on the ribosomal gene sequences and phylogenetic analysis, the fungal strains were identified. Two fungal strains were found to be the same and hence named as Aspergillus terreus strain NTMSK1 and NTMSK2. The two other strains were identified and named as Trichoderma longibrachiatum strain NTMSK3 and Talaromyces pinophilum strain NTMSK4. All isolated fungal species are human pathogens and A. terreus also causes diseases in other animals and plants. The current study demonstrating that cholesterol serves as the carbon source to fungal pathogens opens a new field in fungal pathogenicity and studying of fungal infection mechanisms. Cholesterol and its homologs including phytosterols are ubiquitous in nature as much as cholesterol is an abundant lipid in the human body. Hence, unravelling the cholesterol degradation pathway in fungi will catalyse the development of novel fungal drug targets against animals (including humans) and plants pathogens. Considering the novel concept of fungal utilization of cholesterol, further experiments are under progress (as part of PhD) that will enable this study to be published in high impact factor journal. Microbiology is one of the broadest branches of biology. As a master’s student, I took an initiation and obligation of supervising B Tech students as my contribution for inspiration and development of not only myself as a growing researcher, but of other potential researchers and scientist. Our Unit of Drug Discovery Research (UDDR) specialises among other fields in microbial P450s, therefore the outputs are the following papers, conference proceeding and awards:
Published Thesis